Interview with Patrik Aspers: “Since There Are So Many Theories, We Should Focus on Really Good Empirical Research Instead” - Patrik Aspers (Экономическая социология, 2016)
Patrik Aspers is professor of sociology at Uppsala University (Uppsala Universitet). Maya Shmidt conducted this interview in Uppsala, Sweden, in September 2016.Aspers introduces readers to different academic paths by presenting his own experience of becoming a sociologist and comparing the structural and cultural differences between the American, British, and European academic contexts. During the conversation, Aspers discusses the field of economic sociology and highlights opportunities for interdisciplinary cooperation. Particularly, he notes that sociology has exported certain ideas to other disciplines, and due to the field’s enduring tradition, extensive theoretical literature and ability to distinguish between and combine different research methods, there is no danger of “blurring” within cooperative efforts.Influenced by Harrison White’s theory, Aspers develops a typology of different market forms. He argues that markets, when taken apart, do not look the same: they take different forms, and each requires its own construction of theoretical concepts that can account for the variety in the empirical reality.Aspers emphasizes the significance of clarifying and reflecting upon knowledge as elements of pre-study (“vorstudie”) when it comes to qualitative research. He develops an empirical phenomenology method and presents it as a step-by-step procedure for conducting qualitative research.